Compact MIMO antenna with high isolation technique for 16GHz application / Hamizan Yon - Yon, Hamizan (2023)
Microstrip antenna is an antenna type that most researchers use for multiple input multiple output (MIMO) technology developments. However, some limitations need to be considered when using this type of antenna, such as this antenna has a narrowband characteristic. Currently, several designers have proposed their antennas to improve antenna bandwidth. Hence, proper antenna modifications are required to enhance the antenna’s performance, especially for MIMO systems. Existing works on the MIMO antenna development mostly focus on reducing mutual coupling and improving isolation between antennas, and some conducted studies on the compactness of the MIMO antenna development for modern communication. While the focus has been on designing a compact antenna, a very minimal study has been done on works related to single element with multiport antenna designs. This research aims to develop a wider bandwidth of a single element and a MIMO antenna with lower isolation which is compact for 16GHz systems. The parametric study on the integration technique with parasitic elements through experimental validation was conducted to prove the findings. Furthermore, the present study also analysed the proposed antenna in the MIMO diversity environment through measurements and validations using numerical evaluation.